2020
DOI: 10.1061/(asce)st.1943-541x.0002826
|View full text |Cite
|
Sign up to set email alerts
|

Shear Capacity of Reinforced Concrete T-Beams Retrofit with Externally Bonded CFRP Fabric: A New Perspective

Abstract: Unanchored U-wrapped externally bonded carbon fibre reinforced polymer (CFRP) fabrics are widely used to increase the design shear strength of existing reinforced concrete slab-on-beam structures, but current design models do not accurately predict the degree of enhancement. Experimental investigations further indicate that some T-beams retrofit with externally bonded CFRP fabric fail at lower shear loads than nominally identical un-retrofit reference counterparts, suggesting a negative experimental CFRP 'cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Assessment of the shear capacity of RC beams strengthened with externally bonded Fiber-Reinforced Polymer (EB-FRP) is still a topic widely debated in the literature [1][2][3][4]. As a matter of fact, it is challenging to account, and thus they overestimate the effective contribution to the shear capacity provided by the steel stirrups.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of the shear capacity of RC beams strengthened with externally bonded Fiber-Reinforced Polymer (EB-FRP) is still a topic widely debated in the literature [1][2][3][4]. As a matter of fact, it is challenging to account, and thus they overestimate the effective contribution to the shear capacity provided by the steel stirrups.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fiber-reinforced polymer sheets is a well-studied area of research for RC T-beams and, in particular, many experimental campaigns have been carried out for monotonic loading, e.g., [11,12]. Etman [13] showed that strengthening RC T-beams in the shear zone using carbon-fiber-reinforced polymer (CFRP) enhanced the shear capacity of existing RC beams, which showed that the use of the CFRP sheet reflected higher specimen stiffness, compared to steel.…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening of reinforced concrete (RC) elements is becoming a topic of increased importance due to the ageing of the European building stock and the associated need for building renovation to comply with modern standards, changes of use or the deterioration of materials. For RC beams, the use of fibre-reinforced polymer (FRP) sheets is a well-studied area of research and in particular a large number of experimental campaigns have been carried out for monotonic loading, e.g., [1][2][3][4][5][6][7][8][9][10]. Interest is also growing in other composite materials, such as textile-reinforced mortars (TRM), e.g., [11][12][13] or steel-reinforced grout (SRG) [14][15][16][17] for strengthening RC beams.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of conservatism in design equations has also been noted in other experimental investigations [4], indicating that design equations for transversal FRP strengthening in most design codes depend largely on an FRP to concrete bond model, the effective strain of FRP and the width-to-spacing ratio of FRP strips. The lack of a sufficient number of beams with T-sections in the experimental literature has also been observed [9,10]. Experimental evidence however suggests that other important parameters are not sufficiently addressed in any guidelines, including crack patterns, the shear span-todepth ratio [8] and the amount of flexural FRP strengthening [25], as well as the interaction of external FRP and internal steel reinforcement [26].…”
Section: Introductionmentioning
confidence: 99%